Study of platelet activation, hypercoagulable state, and pulmonary hypertension in patients with transfusion-dependent beta-thalassemia - Lanja Othman Haji; Ranan Kardagh Polus; Nawsherwan Sadiq Mohammed (Iraqi Journal of Hematology)
BACKGROUND: Thalassemic patients require lifelong blood transfusions, which can lead to complications such as pulmonary arterial hypertension. The pathogenesis involves hypercoagulability, in which researches on coagulation abnormalities in this regard are limited. OBJECTIVES: The aims of the study was to investigate the mechanism of hypercoagulability and pulmonary hypertension in transfusion-dependent thalassemic patients and compare it with healthy controls. PATIENTS, MATERIALS AND METHODS: This case–control analysis enrolled 50 transfusion-dependent thalassemia patients and 50 healthy controls. Complete blood counts, liver function tests, coagulation markers (P-selectin, protein C, antithrombin III, and fibrinogen), serum ferritin, and transthoracic echocardiography were performed, and blood transfusion/chelation history and splenectomy status were recorded. RESULTS: Thalassemia patients revealed severe anemia, leukocytosis, thrombocytosis, significantly elevated serum ferritin (1957.50 ± 2455.05 g/L), elevated liver enzymes serum glutamic oxaloacetic transaminase (22.01 ± 9.89 U/L), serum glutamic pyruvic transaminase (22.70 ± 9.78 U/L) in comparison to controls, and mean serum P-selectin was significantly higher in thalassemic patients (100.48 ± 53.29 ng/mL). Mean serum antithrombin-III and protein C were significantly lower in thalassemic patients (89.27 ± 16.08 units/h, 86.04 ± 25.21 μg/mL) in comparison to controls. CONCLUSIONS: Transfusion-dependent thalassemia is characterized by severe anemia and splenomegaly, leading to complex hemodynamic changes with evidence of platelet activation, hypercoagulable state, liver injury, and increased atherosclerosis. It induces pulmonary artery thrombosis contributing to the development of pulmonary artery hypertension.